Mencabar Kebenaran Teks: Menelisik Kelindan “Hanjuang Di Kutamaya” Dalam Naskah Dramatari Dan Kawih Sunda - Lilis Sumiati; Eti Mulyati; Pradasta Asyari (PANGGUNG, 2025)
Every artwork  is viewed  as a network of interconnected meaning, forming a dynamic structure akin to a spider's web. This view is reflected in Dance Drama and Sundanese Kawih, both of which adapt the Jaya Perkosa episode from the Babad Sumedang script. To analyze this relationship, the intertextuality approach is employed to trace the interlocking texts and meanings. On the other hand, the critical discourse approach is used to dissect how both voice criticism and discourse are shaped by the historical relations. As a result, the two works reproduce the content of the Babad Sumedang to reflect current social, political, and cultural conditions. Intertextuality contributes to connecting old texts with contemporary contexts, thereby facilitating a meeting between tradition and modernity. This process demonstrates that cultural texts are continually in dynamic negotiation with an ever-evolving reality.